The Influence of School Principal Supervision and Work Motivation on the Work Discipline of Vocational School Teachers: A Case Study at Public Vocational High School in Batang Regency - Trihandayani, Ifa; Nurkolis, Nurkolis; Haryati, Titik (Journal of Educational Sciences, 2025)
This study aims to examine the influence of principal supervision and work motivation on teachers’ work discipline at public vocational high schools  in Batang Regency. Employing a quantitative approach with a correlational design, the research involved 159 teachers selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed through descriptive statistics, classical assumption tests, and simple and multiple linear regression analyses. The findings indicate that principal supervision significantly influences teachers’ work discipline, contributing 95.4% to the variance, with follow-up academic supervision being the most dominant dimension. Work motivation also shows a significant influence, contributing 95.8%, where internal motivation emerges as the primary factor. Simultaneously, principal supervision and work motivation contribute 95.8% to teachers’ work discipline, with time discipline as the leading dimension. This research offers novelty by mapping the contribution of each dimension of the studied variables in a specific context rarely explored quantitatively. The study is limited to public vocational schools within one district and relies on self-reported data, which may involve subjectivity. Future research is recommended to expand the scope, apply mixed-methods designs, and include mediating or moderating variables such as transformational leadership or school culture to gain deeper insights.